Spent lithium manganate batteries for sustainable recycling: A review - Lu, Xinyu; Li, Zongrun; Zou, Jingtian; Peng, Dezhao; Hu, Wenyang; Zhong, Yuanyuan; Li, Pengfei; Su, Shilin; Wang, Xiaowei; Wang, Shubin; Zhao, Zaowen; Zhang, Jiafeng (Frontiers in Materials, 2023)
Lithium-ion batteries (LIBs) account for the majority of energy storage devices due to their long service life, high energy density, environmentally friendly, and other characteristics. Although the cathode materials of LIB led by LiFePO4 (LFP), LiCoO2 (LCO), and LiNixCoyMn1-x-yO2 (NCM) occupy the majority of the market share at present, the demand of LiMn2O4 (LMO) cathode battery is also increasing year by year in recent years. With the rising price of various raw materials of LIBs and the need of environmental protection, the efficient recycling of spent LIBs has become a hot research topic. At present, the recycling of spent LIBs mainly focuses on LFP, LCO, and NCM batteries. However, with the continuous improvement of people’s safety of LIBs, LiMnxFe1-xPO4 (LMFP) batteries show better potential, which also improves the recycling value of LMO batteries. Therefore, this paper reviews current methods of spent LMO recovery, focusing on the characteristics of the recovery and separation process, which can serve as a reference for subsequent research on LMO recovery, increasing environmentally friendly recovery routes. Finally, the future development direction of LIBs recycling is prospected. Overall, this review is helpful to understand the current progress of LMO battery recycling.